Does US Stock Market affect Malaysia Stock Market during Covid-19 Pandemic? - Binti Nizar, Nurhuda; Bahrudin, Nur Zahida; Che Yahya, Norliza; Mohd Rashid, Siti Norbaya; Tehubijuluw, Florentina Kurniasari (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2S1 (2022): Theme: Promoting Financial and Household Resilience, 2022)
The purpose of this study is to explore the possibility of spillovers in return from the US Stock market return to the Malaysia Stock market. VAR models, Granger causality tests, and Generalized Autoregressive Conditional Heteroscedastic (GARCH) models are conducted in this study. This research considers the daily closing price of the Malaysian stock market indexes (FTSE Bursa Malaysia KLCI), spanning from February 4 2020 to 21st Mac 2022. The period of this research allows the empirical analysis during the period of the hike Covid19 cases. The empirical result concludes that return spillover is found to be unidirectional from the US stock market to the Malaysia stock market. The results of this investigation may have important implications regarding international investment, portfolio diversification, and risk management. Research paper Keywords: COVID-19, GARCH, Financial Markets, Malaysian Stock Markets Reference to this paper should be made as follows: Binti Nizar, N., Bahrudin, N. Z., Che Yahya, N., Mohd Rashid, S. N., & Tehubijuluw, F. K. (2022). Does US Stock Market affect Malaysia Stock Market during Covid-19 Pandemic?. Journal of Entrepreneurship, Business and Economics , 10 (2S1), 124–143.